Gamified Islamic Dance Learning Media for Pesantren: An Android-Based Development Study - Asti Tri Lestari; Anggia Suci Pratiwi; Taofik Muhammad; Meiliana Nurfitriani; Juju Masunah (Online Learning In Educational Research (OLER), 2026)
Islamic dance learning at Pesantren (Islamic boarding schools) experiences problems because of insufficient learning materials, a teacher-centered teaching style, and the difficulty in delivering information about physical activities through conventional instruction. This study’s objective is to create an Android app to be used as instructional media for Islamic dance learning with gamification and social learning features. This study employed a Research and Development (R&D) methodology, utilizing a simplified Borg and Gall model (stages 1–5), encompassing needs analysis, product design and development, expert validation, product revision, and finalization. Data were gathered via observation, interviews, focus group discussions, and structured Likert scale questionnaires were administered to media, material, and language validator. The results show a consistent increase in the media aspect from 3.60 to 4.85, the material aspect from 3.75 to 4.95, and the language aspect from 3.80 to 5.00, all reaching the Very good category. This study produces the one of the first validated Android-based media by integrating gamification, the operationalization of Social Learning Theory, and Islamic dance content in the pedagogical tradition of Pesantren. This study confirms that Android-based Islamic dance learning media with gamification through a social learning model with interactive features is offers a novel approach for the Islamic boarding school environment. This study contributes to establishing that gamification elements must be culturally embedded in Islamic values ​​in order to help student participation and motivation.